(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2023)
The research aims to demonstrate the importance of the role of auditing participation contracts and its impact on sustainable development, since participation are contracts that allow the public sector to contract with the private sector to finance, construct, operate and maintain one of the infrastructure projects from projects that were originally assigned to the public sector to carry out and share the resulting risks between the two sectors. public and private, and that the aim of the participation contracts is to contribute effectively in both sectors to achieving economic and social development, The state is directed towards encouraging and increasing the participation of the private sector in the development plan, through the private sector financing infrastructure projects without increasing the financial burden on the state. Therefore, laws were issued in most countries to regulate the work of the provisions of participation contracts within a legal framework in order to achieve the desired goals of these contracts, which are Benefiting from the expertise of the private sector, training national labor, and transferring modern technology to the country in which projects are to be set up in a more efficient and quality manner. The most important conclusions reached are the lack of integration of the audit procedures applied to the participation contracts due to the weakness of the legal and legislative framework that governs them, which affected the quality of the oversight work and, accordingly, the oversight reports issued by the oversight bodies (the auditor general) in the Federal Financial Supervision Bureau audited and issued Oversight reports on it, and the most important recommendations are the need to take into account the integration of procedures for auditing participation contracts and taking into account the legal frameworks and the regulatory and legal instructions that follow that help those concerned in addressing the oversight, auditing, accounting, legal and regulatory problems that may face the oversight bodies charged with auditing such contracts.